The role of histone deacetylases in human gastrointestinal and associated glands cancer - Masumeh Sanaei; Fraidoon Kavoosi (Fasa University of Medical Sciences, 2019)
Background & Objective: In the eukaryotic cells, the DNA wraps around the histone proteins (H2A, H2B, H3, and H4) and constitutes the nucleosome. Chromatin organization plays a major role in the control of gene expression. Epigenetic modifications can induce a reversible change in the chromatin structure as being open and accessible DNA to the transcriptional factors resulting in gene expression. Histone modification, as an epigenetic factor, is necessary for gene expression. These modifications are concluded in a balance between histone acetyltransferase and histone deacetylase activity. Histone deacetylation compacts chromatin structure resulting in gene silencing. Tumor suppressor genes play an important role in the cancer prevention. Deacetylation of these genes resulting in genes silencing and carcinogenesis. In this review, we will evaluate the effects of histone deacetylases on the gastroinetestinal tract and associated glands cancer. Methods: For this review article, we search different online sources by various researcher motors including Scopus, PubMed, and ISI resulted in finding articles correlated with the effect of histone deacetylase on the gastroinetestinal tract and associated glands cancer. Conclusions: In the current study, we concluded that histone deacetylases can induce cancer by histone deacetylation of tumor suppressor genes in the gastrointestinal tract and associated glands.